Analysis and Business Development Strategy of Mama Indri’s Shop in Kemuning Market, Loa Bakung Village - Utari, Cindy; Candra, Khrisna Purnawan; ., Marwati (JAKADIMAS (Jurnal Karya Pengabdian Masyarakat), 2024)
Along with the development of the times and intense business competition, especially in the culinary field, it is very influential for small businesses such as those in traditional markets. Technological advances in this era of globalization influence the lifestyles of some people towards views about places and brand of products being marketed. There is one small business located in the Kemuning market, Loa Bakung Village named Mama Indri’s Shop which has been operating for 3 years and runs a business in the culinary field such as cake and bread. This study aims to assess business feasibility based on financial aspect as well as formulate a non-financial business development strategies. This study was analyzed using several methods of financial aspects such as the Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), Benefit Cost Ratio (B/C Ratio), and analysis of non-dinancial aspects in the preparation of development strategies using the SWOT method. The result of the business feasibility analysis in this study indicate that Mama Indri’s Shop business is feasible to run with an NPV value of Rp 555,189,428 (NPV>0), IRR of 49% (IRR>the prevailing interest rate), B/C Ratio of 1.60 (B/C>1) and the value of PP/return on capital for 1 (one) Month 29 (twenty nine) Days with a business economic life of 3 years. The acquisition of appropriate non-financial analysis results is an aggressive strategy, namely being in an advantageous situation because has many strengths so that it can take advantageof opportunities in developing the business.